New Procurement Method for Housing Projects Implementing IBS Modular System - Abd Jalil, Ahmad; Nuruddin, Azlan Raofuddin; Jaafar, Mastura; Othuman Mydin, Md Azree (2015)
One of the significant contributors to Malaysian gross domestic product is housing projects. To increase the effectiveness of housing project performance, the Malaysian National Housing Policy identified several strategies including Strategic Thrusts 3 and 5 which is through research and development. The adoption of industrialised building system (IBS) has been recognized as one of the steps under this policy but progress has been very slow. Despite government efforts in introducing the IBS Roadmap as long ago as 2003, no detailed IBS building guidelines or standard regulations for procurement systems or contract documents in terms of tendering, design, construction and operations have been produced. A specific procurement system is required as IBS involves special procedures and processes which are different to traditional methods. Previous researches had concluded that the current traditional and modern procurement methods were not suitable for IBS projects especially in terms of project coordination and payment.